CGRP Receptor Antagonism in COVID-19: Potential Cardiopulmonary Adverse Effects. Issue 1 (January 2021) - Skaria, Tom; Wälchli, Thomas; Vogel, Johannes
Abstract : Recently, the US FDA has authorized a drug repurposing trial with calcitonin gene-related peptide (CGRP) receptor antagonists to reduce lung inflammation in coronavirus 2019 (COVID-19). However, the well-established cardiopulmonary protective effects of CGRP raise concerns about the safety of antagonizing CGRP in COVID-19. Awareness regarding potential cardiopulmonary adverse effects may enable their early detection and prevent illness from worsening.